KUALITAS PELAYANAN KTP GRATIS DI KANTOR KECAMATAN PADANG SELATAN KOTA PADANG - , YANDRY, SSTP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public service is one of the things that should be implemented and fulfilled by the government. The government must be able to provide superior service to meet the desires and needs of the citizen. The number of public complaints towards public service run by the government portrays the disappointing state of public services currently enjoyed by citizens. Free ID card service is an attempt by Padang City Government in improving the quality of public services. This study explored the free ID card service quality and the factors affecting it in the case of free ID card service in Padang Selatan District Office. This is a descriptive study with a qualitative approach. The data used were primary data and secondary data. Primary data collected from interviews and observation while the secondary data acquired from archives or documents related to the problems studied. The results showed that the quality of a free ID card service in the Padang Selatan District Office is not good enough. It can be seen from the office building that have not been repaired after the 2009 earthquake, the lack of supporting means for the services, and unclear procedures and the completion time for ID card service. Applicability of two types of ID card (KTP-el and nonelectronic ID card) also caused misunderstanding and confusion among citizens. ID card service that should have been free also could not be properly implemented. Both officials and the public were not able to succeed the free ID card service program. In addition, there are several factors that affect the poor quality of the free ID card service in the Padang Selatan District Office. One of them was the absence of incentives for personnel thereby reducing their motivation to work and led to extortion. The existing culture in the Padang Selatan public service head office is still contaminated with local custom, habit, and social environment. Personnelâs competency is still lacking